Bach's major vocal works music, drama, liturgy - Rathey, Markus (New Haven Yale University Press, 2016)
"Every year, Johann Sebastian Bach's major vocal works are performed to mark liturgical milestones in the Christian calendar. Written by a renowned Bach scholar, this concise and accessible book provides an introduction to the music and cultural contexts of the composer's most beloved masterpieces, including the Magnificat, Christmas Oratorio, and St. John Passion. In addition to providing historical information, each chapter highlights significant aspects--such as the theology of love--of a particular piece. This penetrating volume is the first to treat the vocal works as a whole, showing how the compositions were embedded in their original performative context within the liturgy as well as discussing Bach's musical style, from the detailed level of individual movements to the overarching aspects of each work. Published in the approach to Easter when many of these vocal works are performed, this outstanding volume will appeal to casual concertgoers and scholars alike." -- Publisher's description.
A female voice : Mary in Bach's Magnificat settings BWV 243 and 10 -- From love song to lullaby : the Christmas oratorio BWV 248 -- Divine glory and human suffering : the St John passion BWV 245 -- The passion and the passions : the St Matthew passion BWV 244 -- Seeing and understanding : the oratorios for Easter and Ascension BWV 249 and 11 -- Between opera and architecture : the B minor mass BWV 232.
Includes bibliographical references (pages ([226]-230) and index.
Keywords: Bach, Johann Sebastian -- 1685-1750 -- Vocal works